2020
DOI: 10.1186/s12889-020-08855-7
|View full text |Cite
|
Sign up to set email alerts
|

Use and awareness of and willingness to self-test for HIV: an analysis of cross-sectional population-based surveys in Malawi and Zimbabwe

Abstract: Background: Many southern African countries are nearing the global goal of diagnosing 90% of people with HIV by 2020. In 2016, 84 and 86% of people with HIV knew their status in Malawi and Zimbabwe, respectively. However, gaps remain, particularly among men. We investigated awareness and use of, and willingness to self-test for HIV and explored sociodemographic associations before large-scale implementation. Methods: We pooled responses from two of the first cross-sectional Demographic and Health Surveys to in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 19 publications
4
27
1
Order By: Relevance
“…Fourteen percent of those who took HIVST kits reported to have never tested for HIV, 98% were men, and of those, 80% were below the age of 35. These results support findings by Johnson et al, where it was found that willingness to self-test by Zimbabwean men was high at around 85% (21). These results are also consistent with other multiple reports that have suggested that HIVST can increase uptake of testing among high risk groups that are under-represented in HIV testing programs (22)(23)(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 92%
“…Fourteen percent of those who took HIVST kits reported to have never tested for HIV, 98% were men, and of those, 80% were below the age of 35. These results support findings by Johnson et al, where it was found that willingness to self-test by Zimbabwean men was high at around 85% (21). These results are also consistent with other multiple reports that have suggested that HIVST can increase uptake of testing among high risk groups that are under-represented in HIV testing programs (22)(23)(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 92%
“…Participants self-reported the information regarding the risk for HIV. Individuals exposed to any of these factors were classified as "high risk"; the remaining participants were classified as "low risk" if they did not report any sexual activity in the past 6 weeks and as "moderate risk" if otherwise (9,21,22). Educational level was categorized according to the educational system of the DRC, as follows: (i) low: unschooled or attending primary school; (ii) middle: attending college (training of 6 years) or technical school (training of 4 years); and (iii) high: attending bachelor's degree, graduate degree (training of 2 years after Bachelor's degree), or postgraduate degree, as previously reported ( 6).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 2, multivariate analysis showed that male gender (adjusted OR: 0.7, 95% CI: 0.5-0.9) was significantly £ High risk for HIV infection was defined as a history of unprotected sex with one or more partners in the past 6 weeks as well as exposure to any of the following high-risk factors in the previous 6 months: multiple (i.e., >2) partners; homosexual intercourse (asked of men); receipt of gifts, cash, or other compensation in exchange for sex (asked of women); or infection with another sexually transmitted disease. Individuals exposed to any of these factors were classified as "high risk"; the remaining participants were classified as "low risk" if they did not report any sexual activity in the past 6 weeks and as "moderate risk" if otherwise (9,21,22).…”
Section: Overall Linkage To Carementioning
confidence: 99%
“…�2) partners, homosexual intercourse (asked of men), receipt of gifts, cash, or other compensation in exchange for sex (asked of women), or infection with another sexually transmitted disease. Individuals exposed to any of these factors were classified as "high risk"; the remaining participants were classified as "low risk" if they did not report any sexual activity in the past six weeks, and as "moderate risk" otherwise [21,22].…”
Section: Study Population and Recruitmentmentioning
confidence: 99%